PENGUKURAN KINERJA KARYAWAN BERDASARKAN LAYANAN KESEHATAN PADA PUSAT KESEHATAN MASYARAKAT MEDOKAN AYU - Putri, Dinda Pradina Berliana; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The purpose of the research which has been done on Medokan Ayu Public Health Clinic Surabaya is to find outhow the public assessment to the medical care services which has been performed by the employees of PublicHealth Clinic and to find out how the services which have been provided by the employees of Public HealthClinic to the community who have become the customers of Medokan Ayu Public Health Clinic Surabaya. Thetechnique has been carried out in analyzing the performance of the employees the Public Health Clinic by usingCommunity Satisfaction Index (CSI). The result of the survey which has been conducted at Medokan AyuPublic Health Clinic Surabaya about how the employee performance in providing medical services which hasbeen conducted to the community each of the survey has indicator, i.e.: (1) service procedures, (2) terms ofservice, (3) service personnel clarity, (4) service personnel disciplinary, (5) service personnel responsibility, (6)service personnel ability, (7) service duration, (8) service equality, (9) service personnel courtesy, (10) servicecharge reasonableness, (11) service charge suitability, (12) service precision execution, (13) environmentalcomfort, (14) security level are in excellent position with overall average index is 3.27 and it shows thecommunity satisfaction index after it has been converted is 81.73 which means that overall the services whichhave been provided by Medokan Ayu Public Health Clinic Surabaya gain excellent mark.Keywords: Performance measurement, community satisfaction index, medical services